Clinical Evaluation of a Novel On-Strip Calibration Method for Blood Glucose Measurement. (July 2014) - Noble, Michael; Rippeth, John; Edington, David; Rayman, Gerry; Brandon-Jones, Sarah; Hollowood, Zoe; Kew, Simon
This study evaluated a novel technology for improving accuracy of self-monitoring of blood glucose (SMBG). The technology calibrates each and every test by measuring the response from a predetermined amount of glucose present in the sample chamber of each test strip. SMBG test strips were modified to include a lid coated with a fast dissolving formulation containing glucose. These test strips were characterized for hematocrit (Hct) and temperature induced error response to develop a calibration algorithm. The modified test strips were used in a clinical evaluation involving fingerstick blood samples from 160 subjects. Experiments involving Hct and temperature induced errors show that the technology generates a signal characteristic of the error conditions in any particular test, but independent of glucose concentration, allowing a correction algorithm to be derived. The approach substantially reduced Hct and temperature derived errors. Clinical evaluation using fingerstick blood directly applied to prototype strips showed the error (measured as MARD) was reduced from 11.1 to 5.9% by the on-strip correction approach and the number of outliers reduced by approximately 90%. This technology could improve the accuracy and precision of glucose monitoring systems and so reduce decision errors particularly in clinical situations where hematocrit and temperature may be significant confounders.